«Transformative constitutionalism» and the European Union? A comparison with Latin American constitutional experiences - Vosa, Giuliano (Diritto Pubblico Europeo - Rassegna online, 2025)
According to a rising narrative, the European constitutionalism should think of itself as a transformative one to counter the drifts towards authoritarian nationalisms both within and outside the EU. Yet, labelling the EU constitutionalism as «transformative» leads to borrowing the conceptual toolkit and imaginary of those stream of constitutional thought already labelled as «transformative», chief among which is the Latin American constitutionalism. Hence, this work wonders what consequences may arise as a result of such borrowing; particularly, whether a sufficient degree of commonality is detectable between the European and Latin American experiences which may justify deploying the «transformative» concept to account for, and provide legitimacy to, the profound changes that have hit the constitutional law of the Union in the last decades